Penanaman Pendidikan Karakter Suku Baduy Muslim Di Lembaga Pendidikan Anak Usia Dini - Robiatul Adawiyah; Heni Novarita; Lita Kurnia; Siti Nurul Aprida (UIN Sultan Maulana Hasanudin Banten, 2024)
Character education is an important foundation that must be applied to children starting from the beginning at the golden age. The purpose of this research is to provide evidence of the life of the Baduy tribe with very obedient/obedient traditions in creating a safe, peaceful, serene, balanced life, which is found in the lives of individuals, families, wider society, religion and the state which is carried out through character education. This research examines the instillation of character education in early childhood of the Muslim Baduy tribe, especially in Nurul Ilmi PAUD which is located in Lembah Barokah Village, Ciboleger Village, Leuwidamar District, Lebak-Banten. This research uses qualitative methods with an ethnographic approach. Data collection techniques were obtained from observation and interviews. The results of the research show that the cultivation of Baduy Muslim character education at the Nurul Ilmi PAUD institution was carried out by introducing good role models, and children were trained in cooperation and children were trained in the qualities of courage. To support the implementation of character education in early childhood, cooperation between teachers, parental support, influential environments and local government is also needed.